A Multiple‐Baseline Study of the Effects Associated With Metacognitive Therapy in Postpartum Depression. (1st February 2013) - Bevan, Denise; Wittkowski, Anja; Wells, Adrian
Abstract : Introduction: Postpartum depression is a disabling psychological disorder that, if left untreated, may have negative consequences for the mother, her partner, and the child. Although women with postpartum depression often experience symptoms of anxiety as well as depression, this has been underresearched. As metacognitive therapy assumes that the underlying mechanisms for both anxiety and depression are the same, it is a potentially useful psychological treatment for postpartum depression. Methods: A pilot study was carried out using a multiple‐baseline single case series to examine the effects associated with metacognitive therapy in the treatment of depression. Six women with postpartum depression were assigned to no‐treatment baselines of 3 to 6 weeks, followed by 8 to 12 sessions of metacognitive therapy. Follow‐up with participants took place at 3 and 6 months posttreatment. Results: All participants experienced clinically significant reductions in symptoms of depression and anxiety, with corresponding reductions in metacognitive beliefs consistent with the idea that this may be the mechanism by which change occurred. Furthermore, all scores fell within the normal range posttreatment, and effect sizes were large. Treatment gains were maintained at 3 and 6 months posttreatment by all participants. Discussion: This pilot study suggests that metacognitive therapy may be an effective psychological treatment for postpartum depression.